A hermeneutic phenomenological study of students' and school counsellors' "lived experiences" of cyberbullying and bullying. (March 2020) - Chan, N.N.; Ahrumugam, P.; Scheithauer, H.; Schultze-Krumbholz, A.; Ooi, P.B.
Abstract: Past studies investigating the phenomenon of cyberbullying employed mainly quantitative methods, yielding significant findings in prevalence rates, patterns of behaviours, coping strategies, and causes. However, there is a need for more qualitative studies to provide the rich details in order to develop a clearer and more congruent concept of cyberbullying. A hermeneutic phenomenological design was used in this study to investigate students' and school counsellors' "lived experiences" of cyberbullying in Malaysia and how they managed these experiences. "Lived experiences" refer to the pre-reflective, immediate consciousness of the experiences which are then subsequently reflected upon and interpreted in hermeneutic phenomenology. The sample consisted of 70 secondary students (ages 13–17 years from 6 national and 1 private schools) and 18 school counsellors (ages 29–57 years). Eight focus groups were conducted over a period of 5 months. The findings revealed that students and school counsellors felt that cyberbullying in most cases existed in a bullying context as their lived experiences revolved around school, out of school and cyberspace lifeworlds; and that any bullying actions perpetuated by cyberbullies/bullies and reinforced by bystanders moved seamlessly from one interconnected lifeworld to another. In particular, the students did not seem to make the difference between bullying and cyberbullying: online space meant the start or continuation of the bullying, which had the intention to harm or mock others. All student participants reported being bystanders in cyberbullying experiences usually in Whatsapp groups and some additionally reported being bullies and victims. Moral disengagement strategies were used by students to justify not taking affirmative action to help victims. Thus, this study further extends the conceptualisation of the phenomenon of cyberbullying and contributes to the field, using qualitative methods. Further research, including perspectives of parents and school administrators, is needed. Highlights: Hermeneutic phenomenology is the methodology used and is original in this study. Students do not differentiate between bullying and cyberbullying in their lifeworlds. Students' interconnected lifeworlds consist of school, out of school and cyberspace. School counsellors expressed a lack of understanding of the nature of cyberbullying. Participant bystanders justified their inaction with moral disengagement strategies.